2020
DOI: 10.1111/ajo.13158
|View full text |Cite
|
Sign up to set email alerts
|

Infertility in Aboriginal and Torres Strait Islander people: A cause for concern?

Abstract: In many Aboriginal and Torres Strait Islander communities, women and men are disproportionately affected by a range of risk factors for infertility including sexually transmitted infections, polycystic ovary syndrome and obesity. However, very little is known about the occurrence of infertility in this group or how Aboriginal and Torres Strait Islander people access fertility treatments. This opinion piece aims to reflect on current evidence concerning infertility risk factors and infertility per se among Abor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…After screening the titles and abstracts, 19 articles fulfilled the inclusion criteria. Full‐text screening identified only 11 papers dealing with the subject of the review 7,8,14‐22 . See Table 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After screening the titles and abstracts, 19 articles fulfilled the inclusion criteria. Full‐text screening identified only 11 papers dealing with the subject of the review 7,8,14‐22 . See Table 1.…”
Section: Resultsmentioning
confidence: 99%
“…The same group, Gilbert and colleagues, 8 also wrote an opinion piece in the same issue, on infertility in Aboriginal and Torres Strait Islander people. They concluded that Indigenous Australians are disproportionately affected by a range of risk factors for infertility including sexually transmitted infections, PCOS, and obesity.…”
Section: Resultsmentioning
confidence: 99%
“…This may be compounded by a reliance on total fertility rate (TFR) as a measure of infertility. The latest national data indicate that the TFR is slightly higher among Aboriginal and Torres Strait Islander women than in the total Australia population; however, this may conceal important differences in rates of secondary infertility 15–17 …”
Section: Discussionmentioning
confidence: 99%
“…The latest national data indicate that the TFR is slightly higher among Aboriginal and Torres Strait Islander women than in the total Australia population; however, this may conceal important differences in rates of secondary infertility. [15][16][17] Anecdotally, our own clinical experiences (J.B.) and informal discussions with Aboriginal Community Controlled Services 18…”
Section: Discussionmentioning
confidence: 99%
“…Despite evidence of elevated risk of infertility, national figures show a higher total birth rate and a younger median age of giving birth for Aboriginal and Torres Strait Islander women compared to all Australian women (2.3 births per woman compared with 1.9 per woman) [ 14 ]. This incongruence between suspected and actual prevalence of infertility for Aboriginal and Torres Strait Islander people raises concerns that the relatively high birth rate could mask significant rates of infertility, with those affected remaining largely undiagnosed and untreated [ 18 ]. This may in part reflect the fact Aboriginal and Torres Strait Islander people have poorer access to and use of mainstream health services, due to barriers such as geographic isolation, the high cost of health care, culture and language differences, and experiences of racism and discrimination [ 19 ].…”
Section: Introductionmentioning
confidence: 99%